Thermalization of electrons in decaying extreme ultraviolet photons induced low pressure argon plasma. (6th April 2016) - Beckers, J; van der Horst, R M; Osorio, E A; Kroesen, G M W; Banine, V Y
Abstract: We monitored—in the pressure range: 0.5–15 Pa—the electron temperature in decaying plasmas induced in argon gas by pulsed irradiation with extreme ultraviolet (EUV) photons with wavelengths closely around 13.5 nm. For this purpose, temporal measurements of the space-averaged and electric field weighted electron density after pulsed EUV irradiation are combined with an ambipolar diffusion model of the plasma. Results demonstrate that electrons are thermalized to room temperature before the plasma has fully expanded to the chamber walls for pressures of 3 Pa and higher. At pressures below 3 Pa, the electron temperature was found to be up to 0.1 eV above room temperature which is explained by the fact that plasma expansion is too quick for the electrons to fully thermalize. The comparison between plasma expansion duration towards a surface, plasma decay at a surface and time needed for thermalization and cooling of electrons is essential for designers of EUV lithography tools and EUV sources since the temperature of electrons dictates many fundamental physical processes.